1938
DOI: 10.1113/jphysiol.1938.sp003687
|View full text |Cite
|
Sign up to set email alerts
|

The air space of the hen's egg and its changes during the period of incubation

Abstract: THE air space of the hen's egg and that of the bird's egg in general, and its changes during the period of incubation, are insufficiently known in many respects, in spite of the fact that its phenomena might be of interest for the study of foetal respiration in the chick. Even its origin is not fully known. According to Lataste [1925] its appearance is the result of contraction of the soft parts from the rigid egg shell as the egg cools after having left the mother's body. Evaporation of water from the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1947
1947
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…The period between the onset of lung ventilation and hatching in the groups P, C and O lasted 23-7, 22-9 and 21-6 hr respectively. These values agree reasonably well with the ones found by Romijn and Roos (1938) and Windle and Barcroft (1938). From Table 3 it appears that the differences in the time of hatching were, on the whole, relatively small.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The period between the onset of lung ventilation and hatching in the groups P, C and O lasted 23-7, 22-9 and 21-6 hr respectively. These values agree reasonably well with the ones found by Romijn and Roos (1938) and Windle and Barcroft (1938). From Table 3 it appears that the differences in the time of hatching were, on the whole, relatively small.…”
Section: Resultssupporting
confidence: 86%
“…This attended by a drastic fall of the O 2 content and a similar rise of the CO 2 content of the air space (Romijn and Roos, 1938). The extreme gaseous composition thus arising will be reached more quickly if the shell is made less permeable.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…During incubation the concentrations in the air cell of the egg of both oxygen and carbon dioxide change. Oxygen concentration falls from 21% at day 4 to 12% at day 20 and the carbon dioxide concentration increases from 0·6% at day 4 to 6% at day 20 (Romijn & Roos, 1938). Therefore, the opening of the air cell of the egg could have had consequences on the embryonic blood gases, influencing CO distribution.…”
Section: The Chick Embryo As a Modelmentioning
confidence: 99%
“…The final L re value is only 1.32 times that of day 10. Romijn and Roos (1938) found that the 'allantoic surface, which lines the floor of the air space' comprises 10-20% of the entire respiratory area of the embryo in the last days of the incubation. In our study, the ratio S ac /S re increases from 0.13 (day 10) to 0.25 on day 20 (Table·3).…”
Section: Discussionmentioning
confidence: 99%